Sources and Distribution of Organic Matter in Coastal Area of Muang Chonburi District, Eastern Thailand: Using Carbon and Nitrogen Stable Isotopes: 10.32526/ennrj/20/202100219 - Boonkwang, Namthip; Boonphakdee, Thanomsak (Environment and Natural Resources Journal, 2022)
The sources and spatial distribution of organic matter were investigated in the nearshore area receiving untreated urban wastewater and offshore areas containing bivalve mariculture in Muang Chonburi District. Content, elemental, carbon, and nitrogen isotopic analyses in particulate organic matter (POM) and surface sediments were performed. We found particulate organic carbon (POC), δ13C, and δ15N of POM ranging from 435.0-5,247.7 µg/L, -27.7 to -22.0 ‰, and 1.7-8.6 ‰, respectively, whereas total organic carbon (TOC), total nitrogen (TN), δ13C and δ15N in sediment were 3.5-76.9 µg/g, 0.8-8.3 µg/g, -25.7 to -22.9 ‰ and 2.6-6.0 ‰, respectively. These values show significant differences between nearshore and offshore sampling stations wherein accumulation of organic matter was high in the nearshore and decreased with greater distance offshore, with some retained in the bivalve farming area. The results from a mixing model indicated that organic matter in POM and sediment were initially derived from anthropogenic organic matter. In contrast to the offshore water which had organic matter derived from marine organic matter. This study highlights the distribution of anthropogenic organic waste released to coastal waters with plenty of bivalve farms such as green mussels and oysters. The results can be used to advise national strategies regarding bivalve aquaculture zoning and seafood safety policies going forward.